Mastery of Trigonometry Material and Its Effect on Students' Ability to Solving Three Dimensional Problems - Nisa Triyatul Fitri; Arif Muchyidin; Reza Oktiana Akbar (Journal of Mathematics Instruction, Social Research and Opinion, 2022)
This study aims to describe whether or not mastery of trigonometry affects students' ability to solve geometric problems in class X at SMAN Kadugede. The form of research used in this study is a quantitative research method. The research design used in this study is a one-shot case study, meaning that the treatment is applied to one experimental group, and then the dependent variable is measured. This design aims to determine a variable's effect on other variables effectively. The data collection instrument used was a test of mastery of trigonometric material and students' abilities in solving three-dimensional space problems. The population in this study was 253 students of class X; in this study, the authors took samples using the cluster random sampling technique with the object sampled in this study, namely class X 4, as many as 34 students at SMA Negeri 1 Kadugede. Analysis of the research data using linear regression test. Mastery of trigonometry material significantly influences mastery of three-dimensional space material. This is indicated by a significant value of 0.000 < 0.05 and the regression equation obtained is Y = 11.435 + 0.758 . The equation means that the ability to solve geometrical problems increases or increases by 0.758 times the mastery of trigonometry material, while the constant value of 11.435 states that if students do not have mastery of trigonometry material, then the ability to solve three-dimensional space problems is shallow. The results of the statistical test showed that there was an effect of mastery of trigonometry material on students' ability to solve three-dimensional problems.